O íbero-ásio-afro-ameríndio e a dimensão pedagógica do cinema negro : pontos reflexivos para análise da construção de uma autoimagem - Santos, Everaldo Silva (2019)
This dissertation was made in the Masters in Education Program of UFMT, on the Social Movements, Politics and Popular Education line of research. It consists of a bibliographical research, with the objective of comprehending the Pedagogical Dimension of Black Cinema, authored by Celso Luiz Prudente (2011, 2014, 2015, 2017), taking into account an educational perspective with the purpose of demonstrating this film trend contributions on resisting racial prejudice that tries to contaminate the African identity, which is essential for any African descendant. As such, it is the possibility of restituting these cultures' images that constitutes this research's problem. Being an exploratory research, it draws from a theoretical referential from the works of Prudente (1995, 2011, 2014, 2015, 2017), as well as theoretical contributions of great relevance such as Bergson (1995, 2005) and Deleuze (1983, 2005) for the categorization of film in general, Freire (1987, 1996) and Vigotski (1993) for dealing with education, and Prudente (2011, 2014, 2015 and 2017) and Duarte (2002, 2009) for the relatiin between film and education. Theorists like Fanon (1968, 2008), Gilberto Freyre (2003) and Césaire (1978, 2006) that contributed to the presentation of a cultural-historical framework in which the colonialism and racism in social thought was developed and focused on film. The results from this research demonstrate a colonial situation in film that portrays a prejudiced imagetic distortion that values eurocentric standards in an attempt to erase the non-European represented in the categories given by Prudente (2011, 2014, 2015, 2017) in the form of the euro-heteromale-authoritarian" and the "iberical-Asian-Afro-Amerind". Overall, the Pedagogical Dimension of Black Film reveals itself in the locus of speech given to the opressed that surpasses the symbolical act of imagetic representation, making it a political act as well. The results also show that black film has an efficient language that explores humanity objectively and subjectively in the same manner it transformed its reality, it shaped its image. By being a phenomenon capable of interacting with social and human aspects, black films, as a cinematographical experience, can be understood as the development of learning that situates itself in the interest of education sciences.